Class Management System Design Desktop Based - Shafa Nurul Aisyah1; Elvi Hana Nabila; Rizky Basatha; Nisa Dwi Septiyanti (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2025)
Classroom management in Indonesian schools faces inefficiencies from Microsoft Excel-based scheduling, causing data errors and delays for administrators and teachers, particularly digital immigrants. This study aims to design a desktop-based classroom management system using VB.NET and MySQL to enable real-time CRUD operations for students, teachers, courses, scores, and printing. Employing a software development approach with the waterfall model, the population consists of 50 potential users (10 administrators, 40 teachers) at Surabaya State University and partner schools; purposive sampling selected 5 key respondents (2 admins, 3 teachers) with 2+ years manual experience. Instruments include needs analysis documents, flowcharts, ERD, prototypes, and black-box testing sheets; data analysis used qualitative-quantitative triangulation validating functional/non-functional requirements. Results demonstrate 100% validity across 36 scenarios in 7 modules (login, dashboard, student/course/score/teacher management, print), confirming system reliability via Human Centered Design. In conclusion, the system enhances administrative productivity, serving as a practical foundation for digital transformation in education, although limited to desktop use.